Bacteriological and Shelf-Life Characteristics of Canned, Pasteurized Crab Cake Mix - Loaharanu, Paisan (1970)
The bacteriological spoilage characteristics of a canned, pasteurized crab cake mix product stored at various temperatures were investigated. A large number of bacteria, both mesophilic and psychrophilic, survived the pasteurization process. Bacillus and Micrococcus were found to predominate when the product was stored at 30 C (86 F) and 18 C (64 F), whereas Alcaligenes predominated at 2 C (36 F). The product was found to be free of Escherichia coli. Bacterial counts, trimethylamine nitrogen, volatile reducing substances, and ammonia determinations were evaluated as indices of quality for the product. Close correlation was observed between bacterial counts, volatile reducing substance values, and organoleptic tests when the product was stored at 30 C (86 F). The shelf-life of the product was approximately 6 months at 2 C (36 F), 4 days at 18 C (64 F), and 27 hr at 30 C (86 F).